Growth in Switzerland : Can Better Growth Be Sustained? - Gagales, Anastassios (Washington, D.C. : International Monetary Fund, 2002)
Swiss growth performance in the past quarter century has been mediocre. The paper finds that conditional income convergence contributes significantly to slow growth and the poor performance of the domestically oriented sectors has been a drag on growth. However, slow growth is not inescapable. Faster growth would require raising total factor productivity growth, which remains low by international standards, and the investment rate. Further progress in structural reform could sustain the underlying growth rate at about 2 percent in the next few years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet